Description of Streptococcus thalassemiae sp. nov., a Bacterium Isolated from Human Blood - Fatou Samba Diouf; Mamadou Beye; Mapenda Gaye; Babacar Mbaye; Stephane Alibar; Mariema Sarr; Gregory Dubourg; Jean-Christophe Lagier; Cheikh Sokhna; Florence Fenollar; Pierre-Edouard Fournier; Cheikh Ibrahima Lo (International Journal of Microbiology)
Blood is a precious biological liquid that is normally sterile. Therefore, bacteria in the bloodstream are shown a priori anomaly. A blood culture is systematically performed to diagnose the cause of the bacteremia. Indeed, a patient received in our service had a thalassemia major and underwent a genoidentical transplant. Then, a blood test was performed to diagnose a four-day fever. In this context, we have isolated strain Marseille-Q2617 from the blood sample. It revealed a new bacterial strain that belongs to the genus Streptococcus. It is a Gram-positive coccus, nonmotile, and nonspore forming. The major fatty acid found is hexadecanoic acid, with 49.5%. A taxonomic method was used to characterize the strain by studying their phenotypic, phylogenetic, and genomic characteristics. In addition, sequence analysis of the 16S rRNA gene shows that the strain Marseille-Q2617 has 99.94% sequence similarity to Streptococcus mitis. Average nucleotide identity (ANI) analysis for strain Marseille-Q2617T showed the highest similarity of 92.9% with S. mitis. The DNA-DNA hybridization value obtained (50.2%) between strain Marseille-Q2607 and S. mitis, its closest related species, was below the recommended threshold (<70%). Strain Marseille-Q2617T has a genome size of 2.02 Mbp with 40.5 mol% of G + C content. Based on these results, we propose a new species of the genus Streptococcus, for which the name Streptococcus thalassemiae sp. nov., Marseille-Q2617T (=CSUR Q2617 = CECT 30109) was proposed.